On the Performance of Power Splitting-Based SWIPT in Self-Energy Recycling Full-Duplex Relaying Networks - Silva, I. W. G. da; Osorio, D. P. M.; Olivo, E. E. B. [UNESP]; Lopez, O. L. A.; Alves, H.; Latva-aho, M.; Matthews, M. B. (Ieee, 2020)
This paper investigates the outage performance of a cooperative relaying network, where the relay node is considered to be an energy-constrained device so that a power splitting-based simultaneous wireless information and power transfer scheme is employed. The relay is considered to operate in full-duplex (FD) mode so that both energy recycling and information decoding can be performed. For this purpose, the relay is assumed to be provided with two batteries which switch between the power supplying mode and charging mode at each transmission block. In particular, we assume that the self-interference inherent to FD mode is not completely suppressed; it is subject only to passive interference cancellation for self-energy recycling, while it is subject to both passive and active cancellation for information decoding. We derive a tight closed-form approximation to the outage probability for the considered FD mode-based scheme, as well as for the HD mode-based counterpart. We validate the obtained expressions via Monte Carlo simulations. The impact of self-energy recycling in FD mode on the system performance is assessed.